EFFECT OF AQUEOUS AND ALCOHOLIC EXTRACTS OF SOME SPICES ON GROWING OF Asperigillus flavus AND A. parasiticus AND AFLATOXIN PRODUCTION - Salah Omer Ahmad (Mesopotamia Journal of Agriculture)
The effect of aqueous and alcoholic extracts of thyme, ginger and rosemary (garland) on growing of Asperigillus flavus and A. parasiticus and their production of aflatoxins B1 and G1 in solid and liquid media was studied. The extracts were added at 0, 250, 500 and 1000 ug/ml of media and incubated at 28º for 7 days. The percents of growth inhibition of the two fungi were calculated in both media and aflatoxins production was tested in liquid medium. Results showed that the extracts were active on fungi growth inhibition and aflatoxins production. Results also showed that 18-100% and 20.5-100% of fungi growth on solid media was inhibited when the liquid and alcoholic extracts were added, respectively. Whereas, the growth of both fungi in liquid media were decreased by 39.4-100% and 38.8-100% when aqueous and alcoholic extracts were used, respectively, the production of aflatoxin B1 by both fungi was decreased by 20-100% and 22-100% when aqueous and alcoholic extracts were added, respectively. Results also showed that aflatoxin G1 production decreased by 44-100% when aqueous and alcoholic extracts were added, respectively. It has been noticed that thyme and ginger had observed higher activity in fungi inhibition and aflatoxins production than that of rosemary.